Growing Degree Day and Seed Yield Relationships in Mustard (Brassica juncea L.) Under Different Sowing Seasons and Locations of Turkey - Fatma Kayaçetin; Fadul Önemli; Güngör Yılmaz; Khalid Mahmood Khawar; Ahmet Kınay; Halil Hatipoğlu; Mehmet Niyazi Kıvılcım; Nimet Kara; Arzu Köse; Fırat Sefaoğlu; Kadir Aytaç Özaydın (Journal of Agricultural Sciences)
Mustard is grown in mild winter regions as late fall and in hard winter regions as late spring crop. Mustard has high degree of adaptability under wide range of climatic conditions in Turkey. Temperature is an important weather parameter affecting the growth and development of the mustard. The sum growing degree day (GDD) for a growing season is related to plant development which is depends on the accumulation of heat. The aim of this study was to determine the adaptation of mustard, under sowing seasons (spring and fall sowing) and locations in terms of crop growth (emergence, 50% flowering, physiological maturity, and sum growing degree days) and seed yield of mustard. Two-year field experiments in a split-plot design with four replications were carried out during 2013-14 and 2014-15 growing seasons  at eight different ecological locations. These locations included Ankara, Aydın, Erzurum, Eskişehir, Isparta, Tekirdağ, Tokat and Şanlıurfa provinces of Turkey-as classified by Köppen-Geiger ecological conditions. The Brassica juncea L. (mustard seeds) were collected from wild conditions in the Konya province of Turkey. The results showed that, sowing seasons and locations significantly affected seed yield and GDD. The maximum seed yield of 3754.9 kg ha-1 was obtained from Tokat (warm humid) during fall sowing with total accumulated GDD of 1512.1 °C for mustard. Sum growing degree-days accumulated in different sowing seasons and locations occurred between 1132.0 °C and 2285.1 °C depending on the related ecological conditions. Fall season crop in Aydın location had the maximum growing degree days. Overall, fall season accumulated more growing degree days due to longer period of sunshine in comparison to spring season with less sunshine days resulting in longer vegetation period.